Bone marrow suppression induced by systemic radionuclides (153Sm) in metastatic breast cancer patients with bone metastases, its impact on subsequent chemotherapy - Łacko, Aleksandra; Pająk, Katarzyna; Kołodziejczyk, Andrzej; Żebrowski, Jacek; Garncarek, Agnieszka; Filipczyk-Cisarż, Emilia (Contemporary Oncology/Współczesna Onkologia, 2005)
Introduction: Bone metastases are present in approximately 75 percent of breast cancer patients, therefore bones are the most frequent localization of metastases and the only site of metastatic spread in many patients. Treatment of bone metastases remains palliative. The commonly used treatment options include: radiotherapy, bisphosphonate therapy and systemic radionuclides. Purpose: The aim of this study was to assess the safety of systemic samarium ( 153 Sm) in breast cancer patients with widespread bone metastases and the impact of bone marrow suppression induced by ( 153 Sm) treatment on hematologic toxicity of concomitant or subsequent chemotherapy. Materials and methods: Data from ninety metastatic breast cancer patients with bone metastases treated in the Lower Silesia Oncology Centre, who in 2002-2004 received 153 Sm in the Nuclear Medicine Department of the 4th Military Hospital was included in the analysis. Sixty nine (77 percent) patients had bone only disease, while in 26 (23 percent), presence of metastases to other organs was confirmed. Fifty four (60 percent) patients were treated with radiotherapy before systemic radionuclides. The majority (80/90 – 89%) of patients received concurrently bisphosphonates, all patients required analgetics. Results: The treatment with radionuclides was generally well tolerated with short-term asymptomatic bone marrow suppression. In 16 (18%) of patients (5 from the group with disease limited to bones and 11 from the group with metastatic spread to other organs) treated with 153 Sm, chemotherapy was planned or initiated. In 10 (62.5%) patients chemotherapy was delayed for a mean period of 4–8 weeks, then dose intensity had to be reduced due to the prolonged reduction of bone marrow reserve. In 4 (25%) patients chemotherapy was planned but not initiated due to persistent bone marrow suppression, only 2 (12.5%) of patients received the treatment with a cytotoxic drug without delay or dose reduction. Conclusions: Results of this study indicate that in metastatic breast cancer patients, if the clinical benefit from chemotherapy is expected, a caution should be recommended in planning palliative treatment with 153 Sm due to the potential delay of cytotoxic therapy, though pathogenesis of long-term bone marrow suppression is multifactorial and it is unlikely that systemic radionuclides play a key role in myelosuppression.